The Influence of Lean Management on Work Effectiveness and Efficiency and Their Impact on Organizational Performance with Work Environmental as Moderating Variables in Manufacturing Companies - Apriyani, Dessy (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The study aims to determine the effect of lean implementation on work effectiveness and efficiency and its impact on organizational performance moderated by the work environment and is conducted using a quantitative approach with employees from four manufacturing companies in Cikarang as research respondents. From the results of the research conducted, it can be seen that communication has a significant positive effect on work effectiveness and efficiency (0.179), and communication has a significant positive effect on organizational performance with sig. value of 0.268, coordination has a significant positive effect on work effectiveness and efficiency with sig. value of 0.194, coordination does not have an influence on organizational performance with sig. value of -0.154, work effectiveness and efficiency have a significant positive effect on organizational performance with sig. value of 0.654, planning has a significant positive effect on work effectiveness and efficiency (0.192), and planning has no effect on organizational performance with sig. value of -0.016, resource allocation has a significant positive effect on work effectiveness and efficiency (0.209), and resource allocation has no effect on organizational performance with sig. value of -0.014, Structure and Integration has a significant positive effect on work effectiveness and efficiency with sig. value of 0.325, Structure and Integration has a significant negative effect on organizational performance with sig. value of -0.137, the work environment has a significant positive effect on organizational performance with sig. value of 0.358, the work environment cannot moderate the effectiveness and efficiency of work on organizational performance with sig. value of 0.567.